A Comparative Study on Short-Term Effects of Compression Orthosis and Exercises in the Treatment of Pectus Carinatum: A Randomized Controlled Pilot Feasibility Trial - AKYÜZ, GÜLSEREN DERYA; YÜKSEL, MUSTAFA; ERMERAK, NEZİH ONUR; GÜNDÜZ, OSMAN HAKAN (GEORG THIEME VERLAG KG, 2021)
Introduction Pectus carinatum (PC) is a congenital chest wall deformity which is characterized by the protrusion of the sternum and costal cartilages. Although orthotic and exercise therapies are commonly offered by physicians for PC treatment, there is a lack of evidence on the benefits of exercises and how long the orthosis should be worn. The aim of this study is to investigate the effects and feasibility of custom-made compression orthosis and exercises in the treatment of PC. Materials and Methods Patients with PC aged 7 to 17 years old were randomized into three groups: compression orthosis 23hours, compression orthosis 8hours, and control group. All groups received exercises for 1hour a day for 3 weeks. Additionally, compression orthosis 23hours group wore the orthosis for 23hours a day, while compression orthosis 8hours group wore the orthosis for 8hours a day. PC protrusion, pressure of correction, thorax lateral and anteroposterior parameters, external chest wall measurements, and Nuss Questionnaire were evaluated before and after the treatment. Also, adverse effects, retention, and compliance were assessed. Feasibility was evaluated by calculating the percentages of recruitment, retention, and safety. Results The compression orthosis 23hours group showed greater improvements than the other groups. After treatment, all groups showed significant changes in protrusion, pressure of correction, and external chest wall measurements. Adverse events occurred with similar frequency across groups. Retention percentages did not differ among groups. Conclusion Compression orthosis use for 23hours can be recommended rather than its use for 8hours because 23hours of orthosis use has better correction and similar adverse effects.
Keywords: exercise; physical therapy; pectus carinatum; compression orthosis; rehabilitation